Rancang Bangun Aplikasi Penanganan Komplain Menggunakan Administrative Workflow System - Muhajir, Afifuddin; Tjandrarini, A. B.; Susilo, Tegar Heru (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract : In running the business process PT PetroKimia Gresik already use information technology (IT) in the form of hardware and software are handled by the IT department. Problems that occur in the use of hardware and software by other departments (external unit) submitted a complaint to the IT department. Complaint handling process is happening now is not well documented because there is no standardization of document complaints, resulting in complaints data search takes a long time. Also the head part and the external unit can not monitor the handling of complaints. Based on these issues, then made the complaint handling applications using administrative workflow system (AWS). AWS to run their activities by providing information to the user through a notification that contains instructions and comments about the activities to be done. The results showed that the application of complaint handling can help IT departments, this can be proved by the test results stating that the function can run 100% in accordance with existing procedures. Then test the results obtained 86.95%. This means the application to handle complaints can be declared fit for use.